The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1007/s11250-013-0361-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessing carcass and meat characteristics of Damara, Dorper and Australian Merino lambs under restricted feeding

Abstract: Seasonal weight loss (SWL) is the most pressing constraint in ruminant production systems in tropical climates. SWL is controlled using supplementation, which is costly and difficult to implement in extensive systems, or using breeds adapted to tropical hot dry climates, like the Damara and Dorper. Albeit 15 years in Australia, little is known on how these sheep compare to Australian Merino. Here, the responses of the Damara, Dorper and Merino breeds to nutritional stress were compared. Seventy-two 6-month-old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
38
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 22 publications
4
38
0
Order By: Relevance
“…Dorper and Damara breeds seem to be more tolerant to feed restriction. Previous studies on these animals713 (Supplementary Table S8) already suggested this tendency. Variations in the carcass weight and yields and in the dimensions of eye muscle were similar in Dorper and Damara breed, and both different of what was observed in Merino.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…Dorper and Damara breeds seem to be more tolerant to feed restriction. Previous studies on these animals713 (Supplementary Table S8) already suggested this tendency. Variations in the carcass weight and yields and in the dimensions of eye muscle were similar in Dorper and Damara breed, and both different of what was observed in Merino.…”
Section: Discussionmentioning
confidence: 55%
“…Animal production in the tropics and the Mediterranean is strongly affected by pasture scarcity and quality during the dry summer and autumn months, leading to Seasonal Weight Loss (SWL), as we have demonstrated in South Africa34, Western Africa56, Western Australia7 and the Canary Islands89. To counter the effects of SWL, farmers use supplementation to balance the nutritional needs of the animals.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Le Neindre et al (1993) reported variation between breeds in ease of movement through facilities, and differences in reaction style to stressors have also been described (Boissy et al, 2005). Shedding 'hair' breeds such as the Dorper and Damara have grown in popularity over the last 15 years due to reduced labour requirements compared with more traditional breeds such as the Merino (Almeida et al, 2013;Alemseged and Hacker, 2014), and quantitative differences in avoidance behaviours between Dorpers and Merinos have been found (Njisane and Muchenje, 2013). Consequently, breed differences in behaviour are likely to become more apparent and more important for efficient handling of sheep as the balance of breeds changes.…”
Section: Sheep Factorsmentioning
confidence: 99%